PENGEMBANGAN KETERAMPILAN SOSIAL DAN KERJASAMA SISWA MELALUI LAYANAN BIMBINGAN DAN KONSELING : PENDEKATAN COGNITIVE-BEHAVIORAL THERAPY (STUDI KASUS DI SMPIT ANNIDA) - Seprianto, Seprianto; Kardina, Nina (TAZKIRAH, 2025)
Social skills and cooperation abilities are essential aspects in an individual’s life. These skills not only help someone interact effectively with others but also play a significant role in personal and professional success. The research focused on relevant parties, including educators who influence students’ social skills and cooperation. Data was collected through observation, interviews, and documentation. The data analysis employed qualitative descriptive methods to clarify phenomena in society. The research findings indicate that the CBT counseling process plays a crucial role in developing students’ social skills and cooperation at SMPIT Annida. The steps involved in this process include initial evaluation, establishing therapeutic relationships, identifying negative thoughts, changing thought patterns, social skills learning, practical application, monitoring and evaluating progress, reinforcement, collaboration with teachers and parents, as well as follow-up and future planning. CBT at SMPIT Annida yielded supportive results for enhancing students’ social skills and cooperation, such as skill improvement, mindset transformation, increased self-confidence, social relationships, and positive impact on the school environment. This study emphasizes the importance of social skills and cooperation in students’ lives and their implications for CBT approaches in educational settings. Keterampilan sosial dan kemampuan kerjasama merupakan aspek penting dalam kehidupan individu. Keterampilan ini tidak hanya membantu seseorang dalam berinteraksi dengan orang lain secara efektif, tetapi juga berperan penting dalam kesuksesan pribadi dan profesional. jek penelitian adalah pihak-pihak terkait, termasuk pendidik yang berpengaruh terhadap keterampilan sosial dan kerjasama siswa. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Analisis data menggunakan deskriptif kualitatif untuk memperjelas fenomena di masyarakat. Hasil penelitian menunjukkan bahwa proses konseling CBT berperan penting dalam pengembangan keterampilan sosial dan kerjasama siswa di SMPIT Annida. Langkah-langkahnya meliputi evaluasi awal, pembentukan hubungan terapeutik, identifikasi pikiran negatif, pengubahan pola pikir, pembelajaran keterampilan sosial, penerapan praktik, pemantauan dan evaluasi progres, penguatan, kolaborasi dengan guru dan orang tua, serta tindak lanjut dan perencanaan masa depan. CBT di SMPIT Annida memberikan hasil yang mendukung pengembangan keterampilan sosial dan kerjasama siswa, termasuk peningkatan keterampilan, perubahan pola pikir, rasa percaya diri, hubungan sosial, dan dampak positif pada lingkungan sekolah. Penelitian ini menekankan pentingnya keterampilan sosial dan kerjasama dalam kehidupan siswa dan implikasinya dalam pendekatan CBT di lingkungan pendidikan.